Konsep Islamic Parenting Menurut Pemikiran Aisah Dahlan dalam Buku Maukah Jadi Orang Tua Bahagia” Program Magister Pendidikan Agama Islam - Sulastri Sulastri; Hifza Hifza; Ahmad Zabidi (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research is based on technological advancements that are in line with everyday life and children grow up in line with rapidly developing technology, from television to computers, smartphones, mobile devices with advanced technology and various applications. Most of their time spent in digital technology, so there are concerns from parents about the negative impacts on children. The purpose of this study is 1) Understanding the basic foundation Aisah Dahlan's thoughts on Islamic parenting in the book Maukah Jadi Orang Tua Bahagia. 2) Analyzing Islamic parenting methods according to Aisah Dahlan's thoughts in the book Maukah Jadi Orang Tua Bahagia. 3) Analyzing Islamic parenting techniques according to Aisah Dahlan's thoughts in the book Maukah Jadi Orang Tua Bahagia. This study uses a descriptive qualitative approach with the type of Library Research or text study. In this study, the primary data source was taken from Aisah Dahlan's book on Islamic parenting, "Maintaining Happy Parents," and secondary data sources were drawn from various other sources, such as relevant books,and journals related to the research topic. The following conclusions can be drawn from the following: 1) Aisah Dahlan offers an integrated concept of Islamic parenting, based on the teachings of the Quran, Hadith, and the thoughts of Islamic scholars. 2) Aisah Dahlan formulated a concrete method or approach to implementing Islamic parenting, namely through role models, and providing advice and attention. 3) According to Aisah Dahlan, Islamic parenting techniques are practical and applicable, specific parental prayer techniques, and the use of Islamic storytelling.